"You’re Throwing Your Life Away": Sanctioning of Early Marital Timelines by Religion and Social Class - Tevington, Patricia (Social Inclusion, 2018)
In the midst of a shifting economic and cultural landscape, many young adults spend their twenties focused on individual achievement and self-actualization while delaying entrance into social roles such as marriage. Yet religion, particularly Evangelical Protestantism, places a high value on marriage as the legitimate context for sexuality and childbearing—which encourages earlier unions. This article, based on interviews with 87 dating, engaged, and married Evangelical young adults (aged 18 to 29), describes the social reaction to respondents’ marital timelines, which are typically at younger ages than their secular peers. Two sources of strong disapproval emerge. First, secular influences from outside of these respondents’ religious communities are almost unilaterally critical of early marriage plans. Second, even within religious communities, Evangelicals from middle class cultural milieus may face additional disapproval if their family formation plans are interpreted as compromising their educational goals. This article offers important insight on the intersecting roles of religion and social class in shaping the trajectories of young adults.